Effect of sugar palm fibers on the properties of blended wheat starch/polyvinyl alcohol (PVA) -based biocomposite films - A.B.A. Mohammed, Abdulrahman; Hasan, Zaimah; A. Borhana Omran, Abdoulhdi; M. Elfaghi, Abdulhafid; Ali, Yasir Hassan; A.A. Akeel, Norie; Ilyas, R.A.; Sapuan, S.M. (Elsevier, 2023)
Sugar palm fiber has been added to reinforce starch, polyvinyl alcohol (PVA) based film. The effect of reinforcement on different properties has been studied. It has been found that reinforcing plasticized starch/PVA matrix with palm fibers has considerably enhanced physical properties, the density of the polymer declined to 1.21 g/cm3 with untreated fibers and to 1.32 g/cm3 with treated fibers, which created a lighter weight bioplastic, and a reduction occurred in water absorption (for example 3% of treated fiber showed 143% absorbed water after 30 min immersing in water) and water solubility. When compared to the films without fibers filler, films reinforced with fibers demonstrated a c3onsiderable improvement in the crystal profile; at 9% fiber load, it improved over double. Additionally, it has been noted that thermal stability has increased. The existence of treated and untreated fibers in the hybrid matrix revealed 23.3% and 24.6% mass residues at 495 C, respectively. However, this enhancement did not coincide with a rise in mechanical properties, Whilst,